Robust and Highly Efficient Free-Standing Carbonaceous Nanofiber Membranes for Water Purification - Liang, Hai-Wei; Cao, Xiang; Zhang, Wen-Jun; Lin, Hong-Tao; Zhou, Fei; Chen, Li-Feng; Yu, Shu-Hong (Advanced functional materials, 2011)
The removal of dye and toxic ionic pollutants from water is an extremely important issue. A simple filtration process to decontaminate water by employing a free‐standing fibrous membrane fabricated from highly uniform carbonaceous nanofibers (CNFs) is demonstrated. This process combines the excellent adsorption behavior of CNFs and the advantages of membrane filtration over conventional adsorption techniques, which include simple scale‐up, reduced time, and lower energy consumption. Batch adsorption experiments showed that the CNFs exhibited larger adsorption capacities than commercial granular active carbon (GAC) and carbon nanotubes (CNTs) because of their large surface area, high uniformity, and numerous active sites on the surface of nanofibers. Membrane filtration experiments proved that the CNF membranes could remove methylene blue (MB) efficiently at a very high flux of 1580 L m−2 h−1, which is 10–100 times higher than that of commercial nano‐ or ultrafiltration membranes with similar rejection properties. The high permeability of CNF membrane permits stacking of membranes to improve adsorption capacity. In addition, the CNF membranes are easily regenerated and remain unaltered in adsorption performance over six successive cycles of dye adsorption, desorption, and washing. Given the high adsorption and regenerability performance of the CNF membrane, it should have potential applications in water purification. Free‐standing carbonaceous nanofiber (CNF) membranes are used to remove dye pollutants from water in a highly efficient way that combines the excellent adsorption behavior of CNFs (high adsorption rate and capacity) and the functionality of nanofibrous membranes (filtration adsorption with high flux).